Developing and Upgrading Cultural Capital Datasets in the Digitalization and Virtual Platforms of Three Samut Prakan Province Communities: “Bang Sao Thong, Bang Pla, Bang Chalong” - Timmaung, Rattana; Thongkon, Wuthipong; Bumpentan, Patumma; Kwanthong, Kodchaporn (Academic and Research Journal of Liberal Arts (Online), 2025)
This research aims to: 1) explore the cultural capital data of the Sam Bang area (comprising Bang Sao Thong District, Bang Pla Subdistrict, and Bang Chalong Subdistrict of Bang Phli District) in Samut Prakan Province; 2) study the historical roots of the Sam Bang area along both sides of the canal in Samut Prakan; and 3) develop cultural capital data in digital format and create a virtual platform using participatory action research processes. The study employed purposive sampling to engage local scholars, cultural capital entrepreneurs, cultural wisdom inheritors, representatives from local administrative organizations, religious and spiritual leaders, community leaders, teachers, and educational personnel. Research methods included surveys, in-depth interviews, participatory observation, focus group discussions, and the development of a virtual platform.Research findings revealed that: The cultural capital data of the Sam Bang area comprises 153 items: Bang Sao Thong District: 49 items (21 tangible and 28 intangible cultural heritage items) Bang Chalong Subdistrict: 34 items (7 tangible and 27 intangible cultural heritage items) Bang Pla Subdistrict: 43 items (8 tangible and 35 intangible cultural heritage items) An in-depth historical study analyzed changes in the Sam Bang area along both sides of the canal, documenting both positive and negative developments. Significant cultural heritage data was obtained from two major communities: the Muslim community of Darul Ameen Mosque and the old market community along the Samrong Canal, including Pueng Tao Gong Shrine and Thapthim Shrine. These findings were presented as a motion graphic series titled "Development of the Sam Bang Area along Both Sides of the Canal in Samut Prakan." A comprehensive cultural map was created, incorporating tangible and intangible cultural heritage with photographs, videos, and geographical coordinates. This information is accessible through: Website: https://dp.culturalmapthailand.info/GL Facebook: facebook.com/สุขไม่จางที่บางเสาธง-สมุทรปราการ-100731384802383 (6,475 followers) YouTube: <a href="http://www.youtube.com/@%E0%B8%97%E0%B8%B5%E0%B9%88%E0%B8%99%E0%B8%B5%E0%B9%88%E0%B8%AA%E0%B8%B2%E0%B8%A1%E0%B8%9A%E0%B8%B2%E0%B8%87%E0%B8%AA%E0%B8%AD%E0%B8%87%E0%B8%9D%E0%B8%B1%E0%B9%88%E0%B8%87%E0%B8%84%E0%B8%A5%E0%B8%AD%E0%B8%87%E0%B8%AA%E0%B8%A1%E0%B8%B8%E0%B8%97%E0%B8%A3%E0%B8%9B%E0%B8%A3%E0%B8%B2%E0%B8%81%E0%B8%B2%E0%B8%A3">youtube.com/@ที่นี่สามบางสองฝั่งคลองสมุทรปราการ Online exhibition through Spatial Metaverse: Happiness3bangsSamut-Prakan